2010
DOI: 10.1111/j.1600-6143.2010.03062.x
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Conundrum and Liver Transplantation Outcome for Combined Hepatocellular‐Cholangiocarcinoma

Abstract: Combined hepatocellular-cholangiocarcinoma (cHCC-CC) is a rare primary liver malignancy with mixed hepatocellular carcinoma (HCC) and cholangiocarcinoma (CC) histological features. It is almost impossible to obtain an accurate, preoperative noninvasive diagnosis of cHCC-CC with tumor markers or crosssectional abdominal imaging due to the mixed histological features. Despite these difficulties, accurate cHCC-CC diagnosis remains an important goal with prognostic significance. In our study, we retrospectively re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 27 publications
3
65
1
1
Order By: Relevance
“…This incidence might have been higher if only patients who had undergone transplantation for HCC had been considered. Panjala et al 6 recently reported that among patients who underwent LT for HCC, 12 patients were found to have mixed HCC-CC and I-CC in the explant. The tumor recurrence rate was 58%, and the 5-year overall patient survival rate was a dismal 16%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This incidence might have been higher if only patients who had undergone transplantation for HCC had been considered. Panjala et al 6 recently reported that among patients who underwent LT for HCC, 12 patients were found to have mixed HCC-CC and I-CC in the explant. The tumor recurrence rate was 58%, and the 5-year overall patient survival rate was a dismal 16%.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 CC tumors are divided into hilar/perihilar and intrahepatic subtypes. Intrahepatic cholangiocarcinoma (I-CC) is rare in patients with cirrhosis with etiologies other than primary sclerosing cholangitis (PSC).…”
mentioning
confidence: 99%
“…Both HCC and ICC have characteristic imaging features. [16][17][18][19] The imaging features of cHCC-ICC are often only subtly different 9,20 from HCC and ICC, precluding reliable imaging diagnosis. Moreover, even percutaneous biopsy of cHCC-ICC may be misleading because only the dominant HCC or ICC component of cHCC-ICCC is confirmed pathologically, and the true histopathology of cHCC-ICC can only be confirmed after evaluation of the resected surgical specimen.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, clinical consensus opposes the use of transplantation as a therapeutic option for patients with these tumors. [8][9][10] However, data regarding optimum management of cHCC-ICC remain murky.…”
Section: Introductionmentioning
confidence: 99%
“…[59][60][61][62][63] One study that analyzed patients in the Surveillance, Epidemiology, and End Results database found that LT (19 patients) and resection (35 patients) for localized combined HCC-CCA had similar 3-y survival rates in the 50% range, which was inferior to LT for HCC (1447 patients, 78%). 63 At the moment, liver resection is preferred over LT for resectable combined HCC-CCA.…”
Section: -52mentioning
confidence: 99%